Exploring Forward-Looking Information Disclosure Practices: Insights from the Malaysian Landscape in the IFRS Era - Almhuob Muftah, Imad H.; Yuserrie, Zainuddin (Human Resource Management Academic Research Society (HRMARS), 2024)
The current study seeks to comprehensively explore Forward-Looking Information Disclosure (FLID) practices in Malaysian firms' annual report narratives. Using a dataset spanning nine years and comprising 1971 firm-year observations, the current study employs visual and statistical analyses to examine the trends and practices of FLID across various industries and the partitioned periods of pre, during and post-IFRS mandatory adoption. The analysis indicates a notable increase in various FLID proxies among Malaysian companies. FLID topics, excluding employee FLID, show steady increases, with a significant surge in 2016 and 2017. Operational FLID is consistently disclosed at higher levels with variations across sample years while accounting and employee FLID topics exhibit the lowest disclosure levels. The Health Care industry leads in FLID, followed by the Utilities industry, whereas Industrial Products and Property industries demonstrate the lowest levels. The RM-ANOVA test highlights significant differences in FLID measures and topics across the three IFRS periods, but no significant differences in mean values for employee FLID. These findings hold potential implications for managers, investors, and policymakers, as they can aid in improving information quality and promoting greater transparency in annual report narratives in the Malaysian context.